Kreativität und soziale Praxis: Studien zur Sozial- und Gesellschaftstheorie - Reckwitz, Andreas (transcript, 2016)
Andreas Reckwitz is one of the most important contemporary German social and cultural theorists. His books, from »The Transformation of Cultural Theories« through to »The Invention of Creativity« have received a broad audience, well beyond the boundaries of sociology. This volume gathers together current essays by Andreas Reckwitz which deal with two ways of approaching a problem: in which ways is late modernity governed by a creativity imperative that forces a corresponding societal structure of aestheticization, innovation and visibility? And what form should a »theory of social practices« take, if it is to guide such an analysis of society?